Nesting habitat of the ‘cupiso’ podocnemis sextuberculata (Testudines: Podocnemididae) in erepecu lake (Pará-Brazil) (2015)
The objective of this study was to identify and describe the nesting habitat of Podocnemis sextuberculata at Erepecu Lake, Trombetas River Biological Reserve, (REBIO-Trombetas; Pará-Brazil). Initially, the main features of the beaches that potentially determine the habitat selection by cupiso for nesting were described. The nests observed on the beaches were recorded, marked and fenced as protection from natural predators. Information regarding date and location was analyzed through simple linear regression for each nest in order to determine relationships between beach features and number of nests. The results showed a positive co-relationship between number of nests and area. Nest site selection by P. sextuberculata in the beaches of the Erepecu Lake could depend on trade-off scenarios among natural threats and a suitable nesting habitat. We also suggest that, due to the high annual hydrologic oscillations, it is possible that the driving factor for habitat selection would be the risks that the females are exposed to while searching for a nesting site, rather than a particular habitat type.